Conversion of Black Carbon Emitted from Diesel-Powered Merchant Ships to Novel Conductive Carbon Black as Anodic Material for Lithium Ion Batteries - Jae-Hyuk Choi; Dae-Yeong Kim; Won-Ju Lee; Jun Kang (Nanomaterials, 2019)
Waste soot generated from diesel engine of merchant ships has ≥ 2 µm agglomerates consisting of 30−50 nm spherical particles, whose morphology is identical to that of carbon black (CB) used in many industrial applications. In this study, we crystallized waste soot by heat treatment to transform it into a unique completely graphitic nano-onion structure, which is considerably different from that of commercial conductive CB. While commercial CB has a large specific surface area because of many surface micropores generated due to quenching by water-spraying in the production process, the heat-treated waste soot has a smooth micropore-free surface. Thus, the treated waste soot acquires the shape of CB but has a much smaller specific surface area. When the treated soot is used as a conductive material in lithium ion battery (LIB) half cells, the Coulombic efficiency of the entire anode is improved significantly owing to its low specific surface area; the electrochemical performance of the LIB is considerably enhanced compared to that of conventional conductive materials. Thus, polluting soot generated in marine propulsion can be transformed into a new class of CB with a unique structure by simple heat treatment; this soot can also be used as an inexpensive conductive material to enhance the LIB performance.